Gastric bypass simultaneously improves adipose tissue function and insulin-dependent type 2 diabetes mellitus - Billeter, Adrian; Vittas, Spiros; Israel, Barbara; Scheurlen, Katharina; Hidmark, Asa S.; Fleming, Thomas; Kopf, Stefan; Büchler, Markus W.; Müller, Beat P. (Langenbeck's archives of surgery, 2017)
ObjectiveThe underlying causes of type 2 diabetes (T2DM) remain poorly understood. Adipose tissue dysfunction with high leptin, inflammation, and increased oxidative stress may play a pivotal role in T2DM development in obese patients. Little is known about the changes in the adipose tissue after Roux-Y gastric bypass (RYGB) in non-severely obese patients (BMI < 35 kg/m2) and since these patients have more T2DM-associated complications than obese patients (“obesity paradox”), we investigated changes in adipose tissue function in a cohort of BMI <35 kg/m2 with insulin-dependent T2DM after RYGB surgery which resolves T2DM.MethodsTwenty patients with insulin-dependent T2DM and BMI <35 kg/m2 underwent RYGB. Insulin-resistance, leptin, oxidative stress, and cytokines were determined over 24 months. Expression of cytokines and NF-kappaB pathway genes were measured in leukocytes (PBMC). Adipose tissue inflammation was examined histologically preoperatively and 24 months after RGYB in subcutaneous adipose tissue.ResultsInsulin-resistance, leptin, oxidative stress as well as adipose tissue inflammation decreased significantly after RYGB. Similarly, systemic inflammation was reduced and peripheral blood mononuclear cells (PBMCs) were reprogrammed towards an M2-type inflammation. Loss of BMI correlated with leptin levels (r = 0.891, p < 0.0001), insulin resistance (r = 0.527, p = 0.003), and oxidative stress (r = 0.592, p = 0.016). Leptin correlated with improved insulin resistance (r = 0.449, p = 0.032) while reduced leptin showed a strong association with improved oxidative stress (r = 0.809, p = 0.001). Lastly, reduced oxidative stress correlated strongly with improved insulin-resistance (r = 0.776, p = 0.001).ConclusionsRYGB improves adipose tissue function and inflammation. Leptin as marker for adipose tissue dysfunction may be the mediating factor between insulin resistance and oxidative stress and thereby likely improving T2DM.
Gesehen am 25.07.2018